Design in four diagnostic language assessments. (July 2015) - Cumming, Alister
The studies documented in the four articles in this special issue uniquely exemplify principles of design-based research as follows: by taking innovative approaches to significant problems in the contexts of real educational practices; by addressing fundamental pedagogical and policy issues related to language, learning, and teaching; and, in the process, by refining their claims and assessment systems. I analyze and compare the four studies in view of Anderson and Shattuck's (2012) guiding principles of design-based research: real educational contexts, design and testing of a significant intervention, mixed research methods, multiple iterations, collaborative partnerships, and practical impact on educational practices. The four studies differ in numerous respects but are mutually informative about conducting systematic inquiry into diagnostic language assessments. The focus of their analyses on distinct aspects of language and communication relevant to particular educational programs and populations suggest that diagnostic language assessments tend more toward specific purposes assessment rather than general language proficiency testing.